Kikuchi-Fujimoto Disease in the United States: Three Case Reports and Review of the Literature - Darcie M Deaver; Mojdeh Naghashpour; Lubomir Sokol (Mediterranean Journal of Hematology and Infectious Diseases)
Kikuchi-Fujimoto Disease (KFD), also known as histiocytic necrotizing lymphadenitis, is a benign, self-limiting disease that manifests primarily as cervical lymphadenopathy but may include low-grade fever, headache, and fatigue.  There is a higher incidence of KFD in women aged 20-35 years and in Asian populations.  A PubMed search revealed 590 articles that described KFD.  Of these, 22 cases have been fully described in the United States.  Ten of the 22 (45%) patients were male and 12 (55%) were female, with 20% Caucasian, 20% Asian American, and the remaining 60% of other ethnic backgrounds.  In this study, we describe an additional 3 cases of KFD and discuss the diagnosis, pathology, and management of KFD.